Kualitas Spermatozoa Dari Semen Beku Sapi Pasundan Post-Thawing Dengan Jenis Pengencer Yang Berbeda - Widaningsih, Rita; Widianingrum, Dini; Somanjaya, Rachmat (Tropical Livestock Science Journal, 2024)
One of the strategies employed to augment the population of Pasundan cattle is the implementation of an Artificial Insemination (AI) program. The efficacy of the insemination process is significantly contingent upon the quality of the spermatozoa following the thawing of frozen semen. The selection of an appropriate frozen semen diluent can enhance the efficacy of the AI process. The objective of this study was to analyze the impact of egg yolk tris and skim milk diluent on the quality of spermatozoa derived from frozen semen of Pasundan cattle following thawing. Additionally, the study aimed to assess the extent of variation in spermatozoa quality produced after thawing, based on the type of frozen semen diluent utilized. The study was conducted using a completely randomized design (CRD). A total of 30 frozen semen samples of Pasundan cattle were randomly assigned to two treatment groups, with 15 replicates in each group. The two treatments were a frozen semen dilution using egg yolk tris and skim milk. The parameters observed included motility, viability, and intact plasma membrane (IPM) of spermatozoa following the thawing of frozen semen. Moreover, to ascertain the extent of the discrepancy between the two treatments, the data were subjected to a t-test. The findings indicated that the use of yellow tris as a diluent resulted in a higher spermatozoa motility rate (p<0.05) compared to skim milk as a diluent (47.73 ± 0.67 vs. 14.16 ± 1.55).  Furthermore, the two types of diluents did not have a significant effect on post-thawing spermatozoa viability (p>0.05). In contrast, the variable of intact plasma membrane (IPM) demonstrated a higher number for the skim milk diluent (p<0.05) than the egg yolk tris (79.71 ± 1.30 vs. 75.59 ± 1.38). The motility of post-thaw spermatozoa is the factor that plays the most pivotal role in the effectiveness of artificial insemination. It can be concluded that egg yolk tris is a superior type of frozen semen diluent for Pasundan cattle, as evidenced by its ability to produce a greater of spermatozoa motility than skim milk diluent.